Unsaturated elasto-plastic constitutive equations for compacted kaolin under consolidated drained and shearing-infiltration conditions - Rahardjo, Harianto (2019)
Transient process of water flow changes the equilibrium conditions of an unsaturated soil, resulting in volume change of a soil. The volume change alters the hydraulic properties of the soil and thus influences the transient process of water flow through the soil. There-fore, the interactive processes between stress-strain behavior and pore-water pressure are the primary processes affecting the mechanical behavior of unsaturated soils. This paper presents coupled elasto-plastic constitutive equations for unsaturated compacted kaolin under consolidated drained and shearing-infiltration conditions. The study focused on the development of the suction increase (SI) yield curve that incorporates changes in matric suction during transient processes. In addition, the relationship of change in specific water volume with respect to net mean stress and matric suction was also proposed by incorporating the hysteresis of soil-water characteristic curve. The simulated results by the proposed constitutive model were compared with those obtained from isotropically consolidated drained tests and shearing infiltration tests of compacted kaolin to verify the proposed model. The simulated results are in close agreement with the experimental results.